2010
DOI: 10.1121/1.3283019
|View full text |Cite
|
Sign up to set email alerts
|

The effect of signal duration on the underwater hearing thresholds of two harbor seals (Phoca vitulina) for single tonal signals between 0.2 and 40 kHz

Abstract: The underwater hearing sensitivities of two 2-year-old female harbor seals were quantified in a pool built for acoustic research by using a behavioral psycho-acoustic technique. The animals were trained only to respond when they detected an acoustic signal ("go/no-go" response). Detection thresholds were obtained for pure tone signals (frequencies: 0.2-40 kHz; durations: 0.5-5000 ms, depending on the frequency; 59 frequency-duration combinations). Detection thresholds were quantified by varying the signal ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 26 publications
(21 reference statements)
2
44
3
Order By: Relevance
“…(1) The data that we obtained on low-frequency temporal processing of tones by a harbor seal do not support the findings of Kastelein et al (2010) (2) The hearing of a harbor seal tested four years following the onset of a small but significant narrowband hearing loss (centered at 5.8 kHz) showed that hearing sensitivity did not improve with extended recovery time following this event. There was no difference in hearing sensitivity to 5.8 kHz signals when thresholds were compared 180 to 1400 days (4+ years) following the appearance of the hearing loss.…”
Section: Resultscontrasting
confidence: 40%
See 2 more Smart Citations
“…(1) The data that we obtained on low-frequency temporal processing of tones by a harbor seal do not support the findings of Kastelein et al (2010) (2) The hearing of a harbor seal tested four years following the onset of a small but significant narrowband hearing loss (centered at 5.8 kHz) showed that hearing sensitivity did not improve with extended recovery time following this event. There was no difference in hearing sensitivity to 5.8 kHz signals when thresholds were compared 180 to 1400 days (4+ years) following the appearance of the hearing loss.…”
Section: Resultscontrasting
confidence: 40%
“…We tested a harbor seal listening for 200 Hz tones of either 500 ms or 2500 ms in a sound-attenuating acoustic chamber to determine if the differences reported by Kastelein et al (2010) would be observed. To do this, highresolution behavioral thresholds were obtained from the seal and reaction times were measured and compared for the two test conditions.…”
Section: Work Completedmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Due to the recent publication of a significant study on temporal processing of acoustic signals by seals (Kastelein et al, 2010), we obtained new data to directly test the hypothesis that seals may show unusually long integration times for low-frequency auditory signals. We tested a harbor seal listening for 200 Hz tones of either 500 ms or 2500 ms in a highly controlled acoustic chamber to determine if the differences reported by Kastelein et al (2010) would be observed.…”
Section: Work Completedmentioning
confidence: 99%
“…Continuous noise is mostly generated by shipping, dredging, sand and gravel extraction, bottom fishing, operational renewable energy, offshore gas and oil platforms, etc.. Impulsive noise has been considered a larger threat to marine mammals than continuous noise (Tasker et al, 2010), although this probably largely depends on the species and its habitat. Since the main marine mammal species in the (southern) North Sea are the harbour porpoise, the harbour seal and the grey seal, extended studies have and are being conducted into the effects of impulsive noise from wind farm piling on these species (and assuming the harbour seal is a good proxy species for grey seals) (Carstensen et al, 2006, Kastelein et al, 2010. Below, we shortly present what currently is known on the occurrence and magnitude of these two types of underwater noise in the North Sea, their sources, and their monitoring and measuring units.…”
Section: Data Availability and Level Of Confidencementioning
confidence: 99%